Complement C4 deficiency--a plausible risk factor for non-tuberculous mycobacteria (NTM) infection in apparently immunocompetent patients. - Hannele Kotilainen; Marja-Liisa Lokki; Riitta Paakkanen; Mikko Seppänen; Pentti Tukiainen; Seppo Meri; Tuija Poussa; Jussi Eskola; Ville Valtonen; Asko Järvinen (PLoS ONE, 2014)
Background Non-tuberculous mycobacteria (NTM) are ubiquitous in the environment and they infect mainly persons with underlying pulmonary diseases but also previously healthy elderly women. Defects in host resistance that lead to pulmonary infections by NTM are relatively unknown. A few genetic defects have been associated with both pulmonary and disseminated mycobacterial infections. Rare disseminated NTM infections have been associated with genetic defects in T-cell mediated immunity and in cytokine signaling in families. We investigated whether there was an association between NTM infections and deficiencies of complement components C4A or C4B that are encoded by major histocompatibility complex (MHC). Methods 50 adult patients with a positive NTM culture with symptoms and findings of a NTM disease were recruited. Patients' clinical history was collected and symptoms and clinical findings were categorized according to 2007 diagnostic criteria of The American Thoracic Society (ATS). To investigate the deficiencies of complement, C4A and C4B gene copy numbers and phenotype frequencies of the C4 allotypes were analyzed. Unselected, healthy, 149 Finnish adults were used as controls. Results NTM patients had more often C4 deficiencies (C4A or C4B) than controls (36/50 [72%] vs 83/149 [56%], OR = 2.05, 95%CI = 1.019-4.105, p = 0.042). C4 deficiencies for female NTM patients were more common than for controls (29/36 [81%] vs 55/100 [55%], OR = 3.39, 95% CI = 1.358-8.460, p = 0.007). C4 deficiences seemed not to be related to any specific underlying disease or C4 phenotype. Conclusions C4 deficiency may be a risk factor for NTM infection in especially elderly female patients.